Distinction between 2'- and 3'-Phosphate Isomers of a Fluorescent NADPH Analogue Led to Strong Inhibition of Cancer Cells Migration - Raoul Manuel; Michelle de Souza Lima; Sébastien Dilly; Sylvain Daunay; Patricia Abbe; Elodie Pramil; Stéphanie Solier; Fabienne Guillaumond; Sarah-Simha Tubiana; Alexandre Escargueil; João Antonio Pêgas Henriques; Nathalie Ferrand; et al. (MDPI AG, 2021)
Specific inhibition of NADPH oxidases (NOX) and NO-synthases (NOS), two enzymes associated with redox stress in tumor cells, has aroused great pharmacological interest. Here, we show how these enzymes distinguish between isomeric 2'- and 3'-phosphate derivatives, a difference used to improve the specificity of inhibition by isolated 2'- and 3'-phosphate isomers of our NADPH analogue NS1. Both isomers become fluorescent upon binding to their target proteins as observed by in vitro assay and in vivo imaging. The 2'-phosphate isomer of NS1 exerted more pronounced effects on NOS and NOX-dependent physiological responses than the 3'-phosphate isomer did. Docking and molecular dynamics simulations explain this specificity at the level of the NADPH site of NOX and NOS, where conserved arginine residues distinguished between the 2'-phosphate over the 3'-phosphate group, in favor of the 2'-phosphate.